Black butler. XXII - Toboso, Yana, 1984- (Yen Press, Hachette Book Group, 2016)
"Escaping the wolves in sheep's clothing of Wolfsschlucht, Earl Ciel Phantomhive, unstoppable butler Sebastian, and the rest of the Phantomhive household abscond with the Emerald Witch. They take refuge in the hideaway of an old family friend--Diedrich, the late Vincent Phantomhive's schoolmate and confidant. But as preparations are made for the passage home to England, word of the Undertaker and his odd behaviour hangs over the proceedings. What little memory could have tripped up the ever-jovial reaper, causing his chartreuse eyes to well with tears...?"--pg.4 of cover.